Analysis of Starr Carter’s Social Actions in The Hare U Give - Khafidaturrafi'ah, Khafidaturrafi'ah (English Literature Study Program, 2024)
Taking action is crucial to achieving our goals. To do that, a variety of actions can be taken. There will be rational or even irrational actions. The purpose of this study was to describe the social action form of the main character, Starr Carten in the novel The Hate U Give, according to Max Weber's Social Action Theory, how she achieved her purposes based on the social action theory, and the impacts of her social actions on her surroundings. This study used a sociological approach with the theory of social action by Max Weber using data sources from a novel entitled The Hate U Give by Angie Thomas. The methodology used is the literary criticism method. Then, the data is collected by reading and noting the relevant data with the theory and research problems. The results obtained from this study are (1) the four types of social action found in Starr Carten's character, which had five instrumentally rational actions, two value-rational actions, seven affectual actions, and two traditional actions. (2) Starr Carten used social action to achieve her purposes by switching her personality, which includes instrumentally rational action that becomes traditional action, and by using her words and voice, which includes incrementally rational and affectual actions. (3) The impact of Starr Carten's social action was when everyone used their voice to defend themselves and change their neighborhood.